COMPROMISE EFFECT ON CONSUMERS’ BEHAVIOR - Markus Surkamta Eric Santosa (Journal of Indonesian Economy and Business (JIEB), 2016)
The way consumers think about the products they will buy determines their buying behavior. The decision to buy a particular product is obviously in accordance with the buyer’s attitude. The buyers will also feel more comfortable if their behavior meets with the approval and expectations of the people close to them. While the development of a certain attitude has no effect on subjective judgment, the effect of compromise is likely to make a contribution to its development. Since it is still unclear, this study’s main purposed is to clarify this. In addition, while an attitude is theorized as being a predictor of behavior, through behavioral intention, the study’s secondary purpose is to boost the earlier findings. Likewise, in accordance with the theory of planned behavior, the study will also examine the other predictors of behavioral intention, in relation to the behavioral intention itself. A sample consisting of a 100 respondents was compiled by using the convenience and judgment technique. The data were analyzed using Amos 16.0 and SPSS 16.0. As expected, the compromise effect had a significant influence on whether the customers’ attitude or the subjective norm was the main determinant. Likewise, the customers’ attitude, the subjective norm and perceived behavioral control were confirmed as good predictors of customers’ behavioral intentions.